2016
DOI: 10.1038/nrmicro.2016.7
|View full text |Cite|
|
Sign up to set email alerts
|

A new view into prokaryotic cell biology from electron cryotomography

Abstract: Electron cryotomography (ECT) enables intact cells to be visualized in 3D in an essentially native state to ‘macromolecular’ (~4 nm) resolution, revealing the basic architectures of complete nanomachines and their arrangements in situ. Since its inception, ECT has advanced our understanding of many aspects of prokaryotic cell biology, from morphogenesis to subcellular compartmentalization and from metabolism to complex interspecies interactions. In this Review, we highlight how ECT has provided structural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 187 publications
(204 reference statements)
1
60
0
Order By: Relevance
“…Though the secretory machinery of these cells has been extensively studied by both LM and conventional EM (Rubi et al, 2005, Giordano et al, 2008), we sought to advance those earlier efforts by imaging these cells in a near-native, frozen-hydrated state in 3-D via electron cryo-tomography (ECT) (Oikonomou and Jensen, 2016). We were particularly interested in dense core secretory granules (DCSGs), intracellular compartments which are central to the efficient secretion of hormones including insulin (Kim et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Though the secretory machinery of these cells has been extensively studied by both LM and conventional EM (Rubi et al, 2005, Giordano et al, 2008), we sought to advance those earlier efforts by imaging these cells in a near-native, frozen-hydrated state in 3-D via electron cryo-tomography (ECT) (Oikonomou and Jensen, 2016). We were particularly interested in dense core secretory granules (DCSGs), intracellular compartments which are central to the efficient secretion of hormones including insulin (Kim et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, due to the large size of the complex and its position spanning the cell envelope, flagellar motors lose components when purified. Recently, the advent of electron cryo‐tomography (ECT) (Gan & Jensen, ; Oikonomou & Jensen, ) allowed our group and others to reveal the in situ structures of various bacterial flagellar motors within intact cells at macromolecular (~4 nm) resolution. These studies showed the diversity of flagellar motors in different species adapted to unique external environments (Chen et al , ; Zhao et al , ; Minamino & Imada, ; Terashima et al , ; Zhu et al , ; Kaplan et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Electron cryotomography (ECT) can image intact cells in a frozen, fully hydrated state, providing macromolecular resolution (~4-6 nm) details about native cellular structures [13]. Here, we used ECT to visualize the structure of the archaellar basal body in vivo in Thermococcus kodakaraensis cells.…”
Section: Introductionmentioning
confidence: 99%